Immunology: Dendritic-cell genealogy. - Laffont, S; Powrie, F (2009)
The differing origins of gut dendritic cells-white blood cells that modulate immune responses-may explain how the intestinal immune system manages to destroy harmful pathogens while tolerating beneficial bacteria. © 2009 Macmillan Publishers Limited. All rights reserved.